FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM - Sri Hermuningsih; Anisya Dewi Rahmawati; Mujino Mujino (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2018)
The purpose of this study is to analyze the factors that affect stock returns on manufacturingcompanies listed on the Indonesia Stock Exchange. The population in this study areManufacturing companies listed on the Indonesia Stock Exchange in the period 2011-2015 atotal of 17 companies sample automotive manufacturing companies sub-sector consisting of 7companies. This sampling technique uses Purposive sampling. The result of research indicatethat: (1) Economic Value Added and systematic risk influence partially influence to stock interestrate return and inflation do not show significant influence. (2) Economic Value Added, systematicrisk, interest rate and inflation simultaneously have a significant effect on stock return level(3) EVA is the most dominant variable affecting stock returns on manufacturing companiescategorized in the automotive sub-company.Keywords: Economic Value Added, Beta Saham, Inflasi, suku bunga, return saham